(untitled) (Islamic Sciences Journal, 2023)
In This Study I Dealt With the Hadiths of The Prophet in Which the word: ((I was a Companion of The Prophet)) Was mentioned and studied them in an analytical study, in terms of explaining the output of the hadith and the translations of the narrators, the verdict on the hadith validity and weakness, the statement of strange words the explanation of the hadith and what is useful from it, These hadiths contain prophetic instructions and great guiding benefits, Which Showed us the great aspect of the prophet’s humility, his caring about guiding the nation and utilizing any appropriate chance for the purpose of guiding and advising.